ANALISIS PENGATURAN PERTANGGUNGJAWABAN PEMBUANGAN LIMBAH CAIR PT.PINDO DELI III DI KABUPATEN KARAWANG - Muhamad Tanto Mulyana; Hana Faridah (Magister Hukum Sekolah Pascasarjana Unida, 2022)
The rapid global economic growth that refers to the era of modernization will have a major impact on companies that affect sectors of human life. In carrying out their business activities, companies often carry out deviant activities that have an impact on all aspects of life and the environment. Seeing the Karawang Regency area being a fast industrial city, and the way the company's waste is managed is quite an important factor for various types of hazardous and toxic waste. Because the quality standards in accordance with the recommendations are not supposed to be dumped directly into the river and become a source of pollution and environmental destruction. The research method used is normative juridical which focuses on the facts that exist in a society. The main data obtained by means of observation and interviews to take a descriptive approach to legal interpretation, namely literature or document studies. In the role supervision of the Department of Environment and Hygiene in Karawang Regency regarding the action of an environmental pollution incident that occurred in the Karawang area without a permit, analysis of environmental impacts and accountability efforts carried out by PT. X for the overflow of the liquid waste, as a form of recovery from the impact of environmental pollution in the Cibeet River and its surroundings